An electrode binder, a method for preparing the same, and an application thereof
Patent Information
- Application Number
- CN202411936869.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing lithium-ion battery adhesives are insufficient in terms of flexibility, resistance to electrolyte swelling, and temperature stability, making it difficult to meet the requirements of high-performance electrode materials.
An electrode adhesive, formulated with a water-soluble polymer and an amino-containing polymer, is prepared through polymerization and alcoholysis reactions to form a cross-linked network structure, thereby improving its adhesion and flexibility.
An electrode adhesive with high bonding strength, low swelling rate and good flexibility has been developed, which is suitable for lithium-ion battery electrode materials and improves the processing performance and performance of the battery.
Smart Images

Figure BDA0005211711200000141 
Figure BDA0005211711200000151 
Figure BDA0005211711200000171
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, specifically to an electrode adhesive, its preparation method, and its application. Background Technology
[0002] In recent years, the rapid development of new energy vehicles has greatly promoted the development of the lithium-ion battery industry. As an essential additive in lithium-ion batteries, binders play two main roles: firstly, they bind scattered active materials into a regular whole, giving the electrode materials good mechanical properties, thus facilitating subsequent processing and production; secondly, they adhere the active materials to the current collector, preventing open circuits caused by active material detachment, thereby ensuring the normal operation of the battery. Therefore, the choice of binder has a significant impact on lithium-ion batteries.
[0003] As an additive, the binder typically constitutes only about 1% of the total electrode material. With such a low addition level, ensuring sufficient performance places extremely high demands on the quality of the binder itself. Firstly, it must possess excellent adhesive properties; secondly, since the binder will be in prolonged contact with the electrolyte during battery operation, it must resist the dissolution and swelling effects of the electrolyte to prevent performance degradation; finally, considering the impact of environmental changes and heat generated by internal resistance during battery use, the binder must exhibit excellent temperature stability.
[0004] Currently, the main negative electrode adhesives used in the market fall into two categories: one is a flexible system using styrene-butadiene latex (SBR) combined with sodium carboxymethyl cellulose (CMC). This system has advantages such as high bonding strength and good flexibility, but also has limitations such as large electrode rebound and high electrolyte swelling rate; the other is a polyacrylic acid (PAA), polyacrylate and its derivatives system. This system has advantages such as high cohesion, low electrolyte swelling rate and high thermal stability, but also has problems such as insufficient flexibility and high processing difficulty.
[0005] Therefore, providing an adhesive with high adhesion, good flexibility, resistance to electrolyte swelling, and high temperature stability is a technical problem that needs to be solved in this field. Summary of the Invention
[0006] To address the above problems, the present invention aims to provide an electrode adhesive, its preparation method, and its application. Compared with the prior art, the electrode adhesive provided by the present invention has good bonding performance, flexibility, and temperature stability, and is resistant to electrolyte swelling, making it suitable for electrode materials of lithium-ion batteries.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides an electrode adhesive, the electrode adhesive comprising a water-soluble polymer and an amino-containing polymer;
[0009] The water-soluble polymer is obtained by sequentially polymerizing and alcoholyzing monomers.
[0010] The monomers include Class I monomers, Class II monomers, and Class III monomers;
[0011] The Class I monomers include vinyl acetate and / or vinyl propionate;
[0012] The Class II monomers include methacrylates containing short-chain alkanes and / or acrylates containing short-chain alkanes;
[0013] The type III monomer contains a cyano group.
[0014] The water-soluble polymer used in the electrode adhesive provided by this invention is obtained by sequentially polymerizing and alcoholyzing monomers. The monomers undergo free radical polymerization to obtain millimeter-sized solid polymer particles, which are then alcoholyzed in a strong alkaline alcohol solution. This process decomposes the ester groups in the alkyl or carboxylic esters of the polymer side chains, leaving hydroxyl and carboxyl groups on the polymer side chains. The linear polymer chains change from lipophilic to hydrophilic, and small molecules are removed by filtration. Therefore, the water-soluble polymer provided by this invention, on the one hand, can form hydrogen bonds with the hydroxyl groups on the surface of the negative electrode material through the hydroxyl groups on its side chains, thereby forming a cross-linked network in the electrode active material and further improving cohesion; on the other hand, the water-soluble polymer provided by this invention contains cyano groups on its side chains, which can effectively improve carrier migration and contribute to improved battery performance. Furthermore, the adhesive provided by this invention uses a blend of the water-soluble polymer and an amino-containing polymer. The addition of the amino polymer provides more cross-linking sites for the linear water-soluble polymer, forming a more robust network structure, effectively dispersing the internal stress of the polymer itself, thereby improving the flexibility and processing performance of the electrode sheet.
[0015] Preferably, the amino-containing polymer includes any one or a combination of at least two of polyethyleneimine, polymelamine, or polymelamine formaldehyde.
[0016] Preferably, the short-chain alkanes in the type II monomers include alkanes with ≤4 carbon atoms. The number of carbon atoms can be, for example, 1, 2, 3 or 4, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0017] Preferably, the Class II monomers include any one or a combination of at least two of methyl acrylate, methyl methacrylate, butyl acrylate, or ethyl acrylate.
[0018] Preferably, the Class III monomers include acrylonitrile and / or methacrylonitrile.
[0019] Preferably, the raw materials for the polymerization reaction further include water, protective colloid, electrolyte and initiator.
[0020] Preferably, the protective adhesive comprises polyvinyl alcohol and / or polyvinylpyrrolidone.
[0021] Preferably, the electrolyte comprises sodium bicarbonate and / or sodium sulfate.
[0022] Preferably, the initiator includes azo compounds and / or peroxides.
[0023] Preferably, the azo compound includes azobisisoheptanenitrile and / or azobisisobutyronitrile.
[0024] Preferably, the peroxide comprises diisopropyl peroxide dicarbonate and / or lauroyl peroxide.
[0025] Preferably, the raw materials for the polymerization reaction, by weight, include 20-70 parts of type I monomers, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or 70 parts, but not limited to the listed values; other unlisted values within the range are also applicable; 10-40 parts of type II monomers, for example, 10, 15, 20, 25, 30, 35, or 40 parts, but not limited to the listed values; other unlisted values within the range are also applicable; 1-20 parts of type III monomers, for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 parts, but not limited to the listed values; other unlisted values within the range are also applicable; and 0.1-0.5 parts of initiator. The following amounts are considered: 1 part, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, or 0.5 part, but not limited to the listed values; other unlisted values within the range also apply. 1-5 parts of protective colloid, for example, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts, but not limited to the listed values; other unlisted values within the range also apply. 0.1-0.5 parts of electrolyte, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, or 0.5 parts, but not limited to the listed values; other unlisted values within the range also apply. 150-300 parts of water, for example, 150 parts, 160 parts, 180 parts, 200 parts, 220 parts, 240 parts, 260 parts, 280 parts, or 300 parts, but not limited to the listed values; other unlisted values within the range also apply.
[0026] Preferably, the mass ratio of the type I monomer, type II monomer, and type III monomer is (40-60):(15-25):(5-15), for example, it can be 40:15:5, 45:17:7, 50:18:9, 55:20:11 or 60:25:15, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0027] In this invention, by optimally controlling the mass ratio of type I monomers, type II monomers, and type III monomers, the proportions of hydroxyl, carboxyl, and cyano groups in the adhesive molecule can be effectively controlled, thereby providing compatibility performance.
[0028] Preferably, the weight-average molecular weight of the water-soluble polymer is 500-1000 kDa, for example, it can be 500 kDa, 550 kDa, 600 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 950 kDa or 1000 kDa, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0029] Preferably, the raw materials for the alcoholysis reaction include a polymer, an alcohol solvent, a strong alkali, and water.
[0030] Preferably, the alcohol solvent includes any one or a combination of at least two of methanol, ethanol, or isopropanol.
[0031] Preferably, the strong alkali includes any one or a combination of at least two of sodium hydroxide, lithium hydroxide, or potassium hydroxide.
[0032] Preferably, the raw materials for the alcoholysis reaction, by weight, include 40-60 parts of polymer, for example, 40, 42, 45, 48, 50, 52, 55, 58, or 60 parts, but are not limited to the listed values; other unlisted values within the range are also applicable; and 180-240 parts of alcohol solvent, for example, 180, 190, 200, 210, 220, 230, or 240 parts, but are not limited to the listed values; other unlisted values within the range are also applicable. The values also apply; 15-30 parts of strong alkali, for example, 15, 16, 18, 20, 22, 24, 26, 28 or 30 parts, but not limited to the listed values, and other unlisted values within the range also apply; 150-300 parts of water, for example, 150, 160, 180, 200, 220, 240, 260, 280 or 300 parts, but not limited to the listed values, and other unlisted values within the range also apply.
[0033] In a second aspect, the present invention provides a method for preparing the electrode adhesive described in the first aspect of the present invention, the preparation method comprising the following steps:
[0034] (1) Polymerization reaction: Polymerization reaction is carried out using type I monomers, type II monomers and type III monomers to obtain polymers;
[0035] (2) Alcohololysis reaction: The polymer obtained in step (1) is subjected to alcohololysis reaction, and then filtered to obtain a water-soluble polymer.
[0036] (3) Dissolution: Mix the water-soluble polymer obtained in step (2) with the solvent to obtain a first solution; mix the amino-containing polymer with the solvent to obtain a second solution;
[0037] (4) Compounding: Mix the first solution and the second solution obtained in step (3) to obtain the electrode adhesive.
[0038] The preparation method provided by this invention involves operations such as polymerization, alcoholysis, dissolution, and compounding. On the one hand, it enables the obtained water-soluble polymer to have groups such as hydroxyl, carboxyl, and cyano groups. On the other hand, it combines the water-soluble polymer with amino-containing polymers to form a more robust network structure. The resulting electrode adhesive helps to improve the flexibility and processing performance of the electrode sheet.
[0039] Preferably, the preparation method specifically includes the following steps:
[0040] (1) Polymerization reaction: Water, protective gel and electrolyte are mixed to obtain mixture A. Initiator and monomer are mixed to obtain mixture B. Mixture B is added to mixture A to carry out the polymerization reaction. Then the mixture is filtered to obtain the polymer.
[0041] (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent to obtain a mixture C. A strong base and water are mixed to obtain a mixture D. Mixture D is added to mixture C to carry out an alcohololysis reaction. Then the mixture is filtered to obtain a water-soluble polymer.
[0042] (3) Dissolution: Mix the water-soluble polymer obtained in step (2) with the solvent to obtain a first solution; mix the amino-containing polymer with the solvent to obtain a second solution;
[0043] (4) Compounding: Mix the first solution and the second solution obtained in step (3) to obtain the electrode adhesive.
[0044] Preferably, the polymerization reaction in step (1) is carried out by suspension polymerization.
[0045] Preferably, the polymerization reaction temperature is 40-70℃, for example, it can be 40℃, 42℃, 45℃, 48℃, 50℃, 52℃, 55℃, 58℃, 60℃, 62℃, 65℃, 68℃ or 70℃, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] Preferably, the polymerization reaction time is 3-5 hours, for example, 3 hours, 3.2 hours, 3.5 hours, 3.8 hours, 4 hours, 4.2 hours, 4.5 hours, 4.8 hours or 5 hours, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0047] Preferably, the temperature of the alcoholysis reaction in step (2) is 10-60℃, for example, it can be 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃ or 60℃, but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 20-50℃.
[0048] Preferably, the alcoholysis reaction time is 1-4 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0049] In this invention, by optimally controlling the temperature and time of the alcoholysis reaction within a specific range, the reaction can be effectively controlled to occur on the polymer side chains rather than the main chain. It is worth noting that when the alcoholysis reaction temperature is too low, the reaction proceeds slowly; when the reaction temperature is too high, the main chain is prone to breakage, generating small molecular fragments and losing its binding effect.
[0050] Preferably, in step (2), an organic solvent is added before filtration to precipitate the water-soluble polymer.
[0051] Preferably, the organic solvent includes ethanol.
[0052] Preferably, after filtration in step (2), the product is further dried and ground to obtain a powdered water-soluble polymer.
[0053] Preferably, the mixing temperature in the preparation of the first solution in step (3) is 50-80℃, for example, it can be 50℃, 52℃, 55℃, 58℃, 60℃, 62℃, 65℃, 68℃, 70℃, 72℃, 75℃, 78℃ or 80℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0054] Preferably, the mixing time in the preparation of the first solution is 1-5 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0055] In this invention, by optimally controlling the dissolution temperature and time during the preparation of the first solution, production efficiency can be effectively improved, ensuring both sufficient dissolution and facilitating production operations. It is worth noting that when the dissolution temperature is too low, the system viscosity can easily become too high, which is detrimental to production transfer.
[0056] Preferably, the solvents of the first solution and the second solution each independently comprise water.
[0057] Preferably, the polymer content in the first solution is 5-15% by mass, for example, 5%, 6%, 8%, 10%, 12%, 14% or 15%, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0058] Preferably, the polymer content in the second solution is 1-20% by mass, for example, it can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0059] Preferably, the mixture in step (4) comprises, by weight, 80-150 parts of the first solution, for example, 80, 85, 90, 95, 100, 105, 110, 105, 120, 125, 130, 135, 140, 145 or 150 parts, but not limited to the listed values, and other unlisted values within the range are also applicable; and 1-10 parts of the second solution, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts, but not limited to the listed values, and other unlisted values within the range are also applicable.
[0060] Thirdly, the present invention provides an application of the electrode adhesive as described in the first aspect of the present invention, the electrode adhesive being used in a lithium-ion battery electrode.
[0061] The electrode adhesive provided by this invention is used in lithium-ion battery electrodes. The hydroxyl groups contained therein can form hydrogen bonds with the hydroxyl groups on the surface of the negative electrode material, thus forming a cross-linked network. Furthermore, the cyano groups can effectively improve carrier migration, which helps to improve battery performance. In addition, the addition of amino polymers can provide more cross-linking sites for linear water-soluble polymers, forming a more robust network structure. Therefore, the electrode adhesive provided by this invention can effectively ensure the processing performance and performance of the electrode, meeting the requirements of lithium-ion batteries.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] (1) The electrode adhesive provided by the present invention uses a self-made water-soluble polymer. The polymer side chain contains abundant hydroxyl and carboxyl groups, which enables it to have good hydrophilicity. The hydroxyl groups on the side chain can form hydrogen bonds with the hydroxyl groups on the surface of the electrode negative electrode material, thereby forming a cross-linked network in the electrode active material and improving its cohesion and adhesion performance. The side chain of the water-soluble polymer contains cyano groups, which can effectively improve carrier migration and help improve battery performance.
[0064] (2) The present invention provides a water-soluble polymer that combines the properties of polyvinyl alcohol and polyacrylic acid, which can further improve cohesion and flexibility.
[0065] (3) The electrode adhesive provided by the present invention uses a water-soluble polymer and an amino-containing polymer compound. The addition of the amino polymer can provide more cross-linking sites for the linear water-soluble polymer, forming a more robust network structure, effectively dispersing the internal stress of the polymer itself, thereby further improving the flexibility and processing performance of the electrode sheet.
[0066] (4) Specifically, the adhesive provided by the present invention, under preferred conditions, can achieve a bonding strength of more than 9.5 N / m after rolling, a swelling rate of less than 17%, and a flexibility of less than 3 mm. Detailed Implementation
[0067] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0068] In the following examples and comparative examples, polyvinyl alcohol was selected from Sichuan Weihua Chemical Co., Ltd., grade 1788; polyethyleneimine was selected from BASF's Lupasol series Lupasol P; and polymelamine resin was selected from Zhanxin's CYMEL series CYMEL350.
[0069] Example 1
[0070] This embodiment provides an electrode adhesive comprising a water-soluble polymer and an amino-containing polymer, wherein the amino-containing polymer is polyethyleneimine, obtained by sequentially polymerizing and alcoholyzing monomers. The monomers include type I monomers, type II monomers, and type III monomers. Type I monomer is vinyl acetate, type II monomer is methyl acrylate, and type III monomer is acrylonitrile. The mass ratio of type I monomers, type II monomers, and type III monomers is 50:15:5.
[0071] This embodiment also provides a method for preparing the above-mentioned electrode adhesive, the method comprising the following steps:
[0072] (1) Polymerization reaction: Water, protective colloid and electrolyte are mixed in a reaction vessel and stirred to dissolve them to obtain mixture A. Initiator and monomer are mixed and stirred to dissolve the initiator to obtain mixture B. Mixture B is added dropwise to mixture A through a peristaltic pump for 3 hours. The polymerization reaction is carried out at 50°C for 4 hours. Then the mixture is cooled and discharged, filtered, and the polymer is obtained.
[0073] (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent and stirred to dissolve, resulting in mixture C. A strong alkali and water are mixed to obtain mixture D. Mixture D is added dropwise to mixture C using a peristaltic pump and alcohololysis reaction is carried out at 50°C for 3 hours. Then the temperature is lowered and 400 parts of ethanol are added to precipitate the water-soluble polymer. After filtration, drying, and grinding, a powdered water-soluble polymer is obtained.
[0074] (3) Dissolution: The water-soluble polymer obtained in step (2) and water are mixed at 70°C for 4 hours to obtain a first solution; the amino-containing polymer and water are mixed to obtain a second solution;
[0075] (4) Compounding: Mix the first solution and the second solution obtained in step (3) and stir continuously for 1 hour to obtain the electrode adhesive.
[0076] In this embodiment, the components used in the preparation method and their amounts are shown in Table 1.
[0077] Example 2
[0078] This embodiment provides an electrode adhesive comprising a water-soluble polymer and an amino-containing polymer, wherein the amino-containing polymer is polyethyleneimine, obtained by sequentially polymerizing and alcoholyzing monomers. The monomers include type I monomers, type II monomers, and type III monomers. Type I monomers are vinyl propionate, type II monomers are butyl acrylate, and type III monomers are acrylonitrile.
[0079] This embodiment also provides a method for preparing the above-mentioned electrode adhesive, the method comprising the following steps:
[0080] (1) Polymerization reaction: Water, protective colloid and electrolyte are mixed in a reaction vessel and stirred to dissolve them to obtain mixture A. Initiator and monomer are mixed and stirred to dissolve the initiator to obtain mixture B. Mixture B is added dropwise to mixture A through a peristaltic pump and the polymerization reaction is carried out at 40°C for 5 hours. Then the mixture is cooled and discharged, filtered, and the polymer is obtained.
[0081] (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent and stirred to dissolve, resulting in mixture C. A strong alkali and water are mixed to obtain mixture D. Mixture D is added dropwise to mixture C using a peristaltic pump and alcohololysis reaction is carried out at 45°C for 4 hours. Then the temperature is lowered and 400 parts of ethanol are added to precipitate the water-soluble polymer. After filtration, drying, and grinding, a powdered water-soluble polymer is obtained.
[0082] (3) Dissolution: The water-soluble polymer obtained in step (2) and water are mixed at 80°C for 3 hours to obtain a first solution; the amino-containing polymer and water are mixed to obtain a second solution;
[0083] (4) Compounding: Mix the first solution and the second solution obtained in step (3) and stir continuously for 1 hour to obtain the electrode adhesive.
[0084] In this embodiment, the components used in the preparation method and their amounts are shown in Table 1.
[0085] Example 3
[0086] This embodiment provides an electrode adhesive comprising a water-soluble polymer and an amino-containing polymer, wherein the amino-containing polymer is polyethyleneimine, obtained by sequentially polymerizing and alcoholyzing monomers. The monomers include type I monomers, type II monomers, and type III monomers. Type I monomers are vinyl acetate, type II monomers are methyl acrylate, and type III monomers are acrylonitrile.
[0087] This embodiment also provides a method for preparing the above-mentioned electrode adhesive, the method comprising the following steps:
[0088] (1) Polymerization reaction: Water, protective colloid and electrolyte are mixed in a reaction vessel and stirred to dissolve them to obtain mixture A. Initiator and monomer are mixed and stirred to dissolve the initiator to obtain mixture B. Mixture B is added dropwise to mixture A through a peristaltic pump and the polymerization reaction is carried out at 70°C for 3 hours. Then the mixture is cooled and discharged, filtered, and the polymer is obtained.
[0089] (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent and stirred to dissolve, resulting in mixture C. A strong alkali and water are mixed to obtain mixture D. Mixture D is added dropwise to mixture C using a peristaltic pump and alcohololysis reaction is carried out at 35°C for 2 hours. Then the temperature is lowered and 400 parts of ethanol are added to precipitate the water-soluble polymer. After filtration, drying, and grinding, a powdered water-soluble polymer is obtained.
[0090] (3) Dissolution: The water-soluble polymer obtained in step (2) and water are mixed at 60°C for 2 hours to obtain a first solution; the amino-containing polymer and water are mixed to obtain a second solution;
[0091] (4) Compounding: Mix the first solution and the second solution obtained in step (3) and stir continuously for 1 hour to obtain the electrode adhesive.
[0092] In this embodiment, the components used in the preparation method and their amounts are shown in Table 1.
[0093] Example 4
[0094] This embodiment provides an electrode adhesive and its preparation method, the only difference from Example 1 is that the alcohol solvent is replaced with methanol.
[0095] Example 5
[0096] This embodiment provides an electrode adhesive and its preparation method. The only difference from Example 1 is that the pH of the alcoholysis reaction remains unchanged, and 20 parts of sodium hydroxide are replaced with 25 parts of lithium hydroxide.
[0097] Example 6
[0098] This embodiment provides an electrode adhesive and its preparation method, the only difference from Example 1 is that the amino-containing polymer is replaced with polymelamine.
[0099] Example 7
[0100] This embodiment provides an electrode adhesive and its preparation method. The only difference from Example 1 is that the total number of monomers remains unchanged, and the number of type I monomer vinyl acetate is adjusted to 28 parts, the number of type II monomer methyl acrylate is adjusted to 28 parts, and the number of type III monomer acrylonitrile is adjusted to 14 parts.
[0101] Example 8
[0102] This embodiment provides an electrode adhesive and its preparation method. The only difference from Example 1 is that the total number of monomers remains unchanged, and the number of type I monomer vinyl acetate is adjusted to 62 parts, the number of type II monomer methyl acrylate is 3 parts, and the number of type III monomer acrylonitrile is 5 parts.
[0103] The components and their amounts used in the preparation methods described in Examples 4-8 above are shown in Table 1. The data in Table 1 represent parts by weight.
[0104] Table 1
[0105]
[0106]
[0107] Example 9
[0108] This embodiment provides a method for preparing an electrode adhesive, which differs from Example 1 only in that the alcoholysis reaction temperature is 10°C.
[0109] Example 10
[0110] This embodiment provides a method for preparing an electrode adhesive, which differs from Example 1 only in that the alcoholysis reaction temperature is 60°C.
[0111] Example 11
[0112] This embodiment provides a method for preparing an electrode adhesive, the only difference from Embodiment 1 being that the mixing time in the preparation of the first solution is 6 hours.
[0113] Comparative Example 1
[0114] This comparative example provides an electrode adhesive and its preparation method. The only difference from Example 1 is that the electrode adhesive is only a first solution and is not compounded with a second solution.
[0115] Comparative Example 2
[0116] This comparative example provides an electrode adhesive and its preparation method. The only difference from Example 1 is that the electrode adhesive is only a second solution and is not compounded with the first solution.
[0117] Performance testing:
[0118] (1) Physical property testing:
[0119] After cooling the adhesive samples prepared in the examples and comparative examples to 25°C, their pH values were tested with a pH meter; their viscosity was tested with a viscometer; 2-3g of adhesive was taken, weighed (recorded as M1), and then placed in an oven at 150°C for 30 minutes, weighed again (recorded as M2), and the solid content was calculated: solid content = M2 / M1 × 100%.
[0120] (2) Bond strength:
[0121] Artificial graphite (electrode active material), conductive carbon black (SP), binder, and water were dispersed at high speed for 1 hour to prepare a viscous slurry (solid content 52 wt%). After standing for 1 hour, the slurry was coated onto copper foil using an automatic coating machine and dried at 105°C for 5 minutes to obtain an electrode sheet. The mass ratio of electrode active material, SP, and binder was 97:1:2, and the areal density of the coated electrode was 8 g / cm³. 2 .
[0122] The electrode sheet was rolled using a roller press at a pressure of 8 MPa, and the peel bond strength before and after rolling was tested. The specific method was as follows: the copper foil electrode sheet was cut into 5cm × 10cm pieces, and the side coated with slurry was adhered to 3M tape. The 3M tape was then attached to a stainless steel plate. After preparing the samples, a universal tensile testing machine was used to fix the stainless steel plate, and the copper foil electrode sheet was peeled 180° from the stainless steel plate. To ensure the accuracy of the results, each sample was tested five times, and the highest and lowest values were removed. The average of the remaining values was taken as the bond strength data.
[0123] (3) Electrolyte swelling resistance:
[0124] Place 15g of adhesive sample into the mold and bake at 65℃ for 72 hours to dry. Then, cut a 1.5×1.5cm section from the middle portion. 2 For a sample with a size and thickness of approximately 3 mm, accurately weigh the sample mass and record it as m1. Immerse the sample in electrolyte and place it at 65℃ for 72 hours. After that, remove the sample, use lint-free paper to absorb the residual liquid on the surface, and weigh the sample mass again and record it as m2. The swelling rate is calculated using the following formula: Swelling rate = (m2-m1) / m1×100%.
[0125] (4) Flexibility test:
[0126] The prepared electrode sheet is tested using a cylinder. The test method is as follows: the cylinder is fixed on the base, the electrode sheet passes through the cylinder, and after a 180° bend, the electrode sheet is removed and the crease at the bend is observed. If there is no obvious mark, it means that it has passed. The test is repeated with a cylinder of a smaller diameter until a crease appears. The smallest cylinder diameter that passes the test is recorded. The smaller the value, the higher the flexibility.
[0127] The data for Examples 1-11 and Comparative Examples 1-2 are shown in Table 2.
[0128] Table 2
[0129]
[0130]
[0131] The following points can be observed from the data in Table 2:
[0132] (1) As can be seen from the data of Examples 1-6, under preferred conditions, the adhesive provided by the present invention can achieve a bonding strength of more than 9.5 N / m after rolling, a swelling rate of less than 17%, and a flexibility of less than 3 mm.
[0133] (2) A comprehensive comparison of the data from Example 1 and Examples 7-8 shows that the only difference between Examples 7-8 and Example 1 is that the mass ratio of Class I monomers, Class II monomers and Class III monomers is not within the preferred range of the present invention. The bonding strength after rolling in Example 1 is significantly higher than that in Examples 7-8, the swelling resistance is significantly better than that in Example 8, and the flexibility is significantly better than that in Example 7. Therefore, the present invention can further improve the overall performance of the adhesive by optimizing and controlling the mass ratio of Class I monomers, Class II monomers and Class III monomers.
[0134] (3) By comparing the data of Example 1 and Examples 9-11, it can be seen that the present invention can further ensure adhesion, swelling resistance and flexibility by preferentially controlling the temperature of the alcoholysis reaction. The present invention can further ensure that the polymer is fully dissolved by preferentially controlling the mixing time in the preparation of the first solution, thereby further improving adhesion.
[0135] (4) Comparing the data of Example 1 and Comparative Examples 1-2, it can be seen that the adhesive provided by the present invention, by using a water-soluble polymer and an amino-containing polymer compound, can improve the bonding strength and flexibility after rolling compared to using only one polymer.
[0136] In summary, the electrode adhesive provided by this invention has good bonding performance and flexibility, and is resistant to electrolyte swelling, making it suitable for electrode materials in lithium-ion batteries.
[0137] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. An electrode adhesive, characterized in that, The electrode adhesive comprises a water-soluble polymer and an amino-containing polymer; The water-soluble polymer is obtained by sequentially polymerizing and alcoholyzing monomers. The monomers include Class I monomers, Class II monomers, and Class III monomers; The Class I monomers are vinyl acetate and / or vinyl propionate; The Class II monomers are methyl acrylate and / or butyl acrylate; The Class III monomers are acrylonitrile and / or methacrylonitrile; The amino-containing polymer is polyethyleneimine; The mass ratio of the Class I monomer, Class II monomer and Class III monomer is (40-60):(15-25):(5-15); The preparation method of the electrode adhesive specifically includes the following steps: (1) Polymerization reaction: Water, protective gel and electrolyte are mixed to obtain mixture A. Initiator and monomer are mixed to obtain mixture B. Mixture B is added to mixture A to carry out the polymerization reaction. Then the mixture is filtered to obtain the polymer. (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent to obtain a mixture C. A strong base and water are mixed to obtain a mixture D. Mixture D is added to mixture C to carry out an alcohololysis reaction. Then the mixture is filtered to obtain a water-soluble polymer. (3) Dissolution: Mix the water-soluble polymer obtained in step (2) with the solvent to obtain a first solution; mix the amino-containing polymer with the solvent to obtain a second solution; (4) Compounding: The first solution and the second solution obtained in step (3) are mixed to obtain the electrode adhesive; The protective adhesive is polyvinyl alcohol; The electrolyte is sodium bicarbonate; The initiator is azobisisobutyronitrile and / or diisopropyl peroxide; The raw materials for the polymerization reaction, by weight, include 40-60 parts of type I monomers, 15-25 parts of type II monomers, 5-15 parts of type III monomers, 0.1-0.5 parts of initiator, 1-5 parts of protective colloid, 0.1-0.5 parts of electrolyte, and 150-300 parts of water. The polymerization reaction is carried out at a temperature of 40-70℃; The polymerization reaction takes 3-5 hours; The alcohol solvent is methanol and / or ethanol; The strong base is sodium hydroxide and / or lithium hydroxide; The alcoholysis reaction takes 1-4 hours; The alcoholysis reaction is carried out at a temperature of 20-50℃. The raw materials for the alcoholysis reaction, by weight, include 40-60 parts of polymer, 180-240 parts of alcohol solvent, 15-30 parts of strong alkali, and 150-300 parts of water. In step (3), the mixing temperature in the preparation of the first solution is 50-80℃; The mixing time in the preparation of the first solution is 1-5 hours; The mixture in step (4) comprises, by weight, 80-150 parts of the first solution and 1-10 parts of the second solution.
2. The electrode adhesive according to claim 1, characterized in that, The weight-average molecular weight of the water-soluble polymer is 500-1000 kDa.
3. A method for preparing an electrode adhesive as described in claim 1 or 2, characterized in that, The preparation method specifically includes the following steps: (1) Polymerization reaction: Water, protective gel and electrolyte are mixed to obtain mixture A. Initiator and monomer are mixed to obtain mixture B. Mixture B is added to mixture A to carry out the polymerization reaction. Then the mixture is filtered to obtain the polymer. (2) Alcohololysis reaction: The polymer obtained in step (1) is mixed with an alcohol solvent to obtain a mixture C. A strong base and water are mixed to obtain a mixture D. Mixture D is added to mixture C to carry out an alcohololysis reaction. Then the mixture is filtered to obtain a water-soluble polymer. (3) Dissolution: Mix the water-soluble polymer obtained in step (2) with the solvent to obtain a first solution; mix the amino-containing polymer with the solvent to obtain a second solution; (4) Compounding: Mix the first solution and the second solution obtained in step (3) to obtain the electrode adhesive.
4. The preparation method according to claim 3, characterized in that, The polymerization reaction in step (1) includes suspension polymerization.
5. The preparation method according to claim 3, characterized in that, In step (2), an organic solvent is added before filtration to precipitate the water-soluble polymer.
6. The preparation method according to claim 5, characterized in that, The organic solvent includes ethanol.
7. The preparation method according to claim 3, characterized in that, After filtration in step (2), the product is dried and ground in sequence to obtain a powdered water-soluble polymer.
8. The preparation method according to claim 3, characterized in that, The solvents of the first solution and the second solution each independently include water.
9. The preparation method according to claim 3, characterized in that, The polymer content in the first solution is 5-15% by mass.
10. The preparation method according to claim 3, characterized in that, The polymer content in the second solution is 1-20% by mass.
11. An application of the electrode adhesive as described in claim 1 or 2, characterized in that, The electrode adhesive is used for lithium-ion battery electrodes.
Citation Information
Patent Citations
Curable composition, bonding method and bonded body
CN101622287A
Water-soluble electrode binder, electrode plate and preparation method thereof, and electrochemical energy storage device
CN108933260A
Aqueous polymer for adhesive and preparation method, aqueous adhesive and silicon cathode lithium ion battery
CN110423301A
Binder composition for anode, anode, and secondary battery
CN113728470A
